Yavar-70A, a novel water-in-oil adjuvant: A potency study in HPV-16E7d vaccine model - Zeinab Mirzaei; Soyar Sari; Masoud Moghaddam Pour; Seyed Mehdi Hassanzadeh; Benjamin Damizadeh; Morteza Taghizadeh; Mehdi Mahdavi (Iranian Journal of Basic Medical Sciences, 2025)
Objective(s): Adjuvants are some of the most important components used for vaccine formulation. In addition, the efficacy of vaccines is highly dependent on the nature of the adjuvants used. Therefore, new adjuvant formulations may help develop more potent vaccines. In the present study, the potency of an in-house and water-in-oil adjuvant (Yavar-70A) was compared with Montanide ISA 206 and Montanide ISA 266 in an HPV-16E7d vaccine model. Materials and Methods: Three HPV-16 E7d vaccines were formulated using three different adjuvants, Montanide ISA 206, Montanide ISA 266, and Yavar-70A, with standard protocols. Afterward, each formulation containing 10 μg of the E7d protein was administered thrice at two-week intervals to C57BL/6 mice. Serum levels of IFN-γ and IL-4 cytokines secreted from spleen cells, total IgG, and specific IgG1 and IgG2a isotypes were assessed using ELISA two weeks after the last immunization. Lymphocyte proliferative responses were also evaluated using the BrdU method.Results: The results indicated that the vaccine formulated using the Yavar-70A adjuvant showed the highest lymphocyte proliferation responses compared with other groups and higher IFN-γ cytokine release compared with that formulated using Montanide ISA 206. However, the vaccine formulated using Montanide ISA 206 induced the highest total IgG responses compared with other groups. Importantly, the vaccine formulated using Yavar-70A decreased IL-4 secretion compared with other vaccinated groups.Conclusion: The present study demonstrated that Yavar-70A induces cellular and humoral immunologic parameters against the HPV-16 E7d vaccine model comparable to commercialized oil-based adjuvants.